Hi,
payalpathakI will explain it step-wise
First, we can simplify the equality to:
T = k*\(\sqrt{\frac{r^3}{X}}\)
Second, separate the variable we want to examine in the LHS, while other variables in the RHS.
\(X = k^2*\frac{r^3}{T^2}\)
third, apply the changes (T become 2T, and r become 2r) to see how X will change:
\(k^2*\frac{(2r)^3}{(2T)^2}\) = \(k^2*\frac{8r^3}{4T^2}\) = \(2*(k^2*\frac{r^3}{T^2})\) \(= 2X\)
so when T and r are doubled, X will become 2X (doubled also)
_________________
..Thanks for KUDOS